2016
DOI: 10.1002/pad.1754
|View full text |Cite
|
Sign up to set email alerts
|

The Pacifying Police Units of the State of Rio de Janeiro (UPPs): Incremental Innovation or Police Reform?

Abstract: This article considers the experience of Unidades de Polícia Pacificadora (UPPs) (Pacifying Police Units) of the State of Rio de Janeiro, Brazil, as an innovative form of policing designed to deal primarily with high crime rate in "favelas." It also attempts to ascertain the extent to which the UPPs reflect a strategy for police reform. It does so by (i) reviewing the security crisis which engendered the UPPs as well as their predecessors, describing the socio-economic hardships of the favelas, further aggrava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The fight against violence has always been one of the most important governments' agendas since the constitution of the first modern States (based on the idea of concentrating military power) until the present day. The specialized literature on violence has focused on studying this broad phenomenon of how States protect their territories and citizens, and fight crime (Brambilla and Jones, 2019;Bond and Gebo, 2014;Ezcurra, 2017;Marenin, 2014;Pinto and Do Carmo, 2016;Weber, 2012). Some studies have also analyzed specific policies against everyday violence, such as policing practices and social work initiatives to protect women, children, and vulnerable groups (Epp et al, 2017;Frattaroli, 2006;Johansen, 2019;Kyed, 2019;Levenson and D'Amora, 2007;Meier and Nicholson-Crotty, 2006;Nicholson-Croty et al, 2017;van Steden et al, 2015).…”
Section: Violence and The State: Issues For Frontline Workersmentioning
confidence: 99%
See 2 more Smart Citations
“…The fight against violence has always been one of the most important governments' agendas since the constitution of the first modern States (based on the idea of concentrating military power) until the present day. The specialized literature on violence has focused on studying this broad phenomenon of how States protect their territories and citizens, and fight crime (Brambilla and Jones, 2019;Bond and Gebo, 2014;Ezcurra, 2017;Marenin, 2014;Pinto and Do Carmo, 2016;Weber, 2012). Some studies have also analyzed specific policies against everyday violence, such as policing practices and social work initiatives to protect women, children, and vulnerable groups (Epp et al, 2017;Frattaroli, 2006;Johansen, 2019;Kyed, 2019;Levenson and D'Amora, 2007;Meier and Nicholson-Crotty, 2006;Nicholson-Croty et al, 2017;van Steden et al, 2015).…”
Section: Violence and The State: Issues For Frontline Workersmentioning
confidence: 99%
“…Therefore, even if violence manifests itself as a widespread phenomenon, it occurs in very different ways in different places and is directed against different social groups (Keenan, 2019; Kyed, 2019; Murphy et al., 2018; Pilo, 2019; Pinto and Do Carmo, 2016; Vigneswaran, 2014). Studies have shown how some groups are more subject to situations of violence, mainly based on their race, gender, ethnicity, religion, or neighborhood (Epp et al., 2017; Mawani, 2012; Nicholson-Croty et al., 2017; Reiss and Roth, 1993; Wade-Olson, 2019).…”
Section: Violence and The State: Issues For Frontline Workersmentioning
confidence: 99%
See 1 more Smart Citation